PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BANK INDEX CABANG BEKASI - Bentari Faka; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this study is to examine the influence of competence and work discipline on the performance of Bank Branch's Bekasi Index employees. The research method used is descriptive and quantitative research method with sample number 50 respondents. Data were collected by using questionnaire method, data instrument test, classical assumption test and data analysis used were linear regression analysis, correlation and coefficient of determination. Test hypothesis Test F. The results showed that the competence and discipline of work have a positive and significant effect on the performance improvement of Bekasi Bank Index employees.